2007
DOI: 10.1158/1078-0432.ccr-07-0320
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repeated Administration of Cyclophosphamide on Cytochrome P450 2B in Rats

Abstract: Purpose: The prodrug cyclophosphamide (CPA) is activated by cytochrome P450 (CYP) enzymes. CPA is one of the corner stones in all cancer treatment. We have studied the effect of repeated doses of CPA given at different time intervals on the mRNA, protein levels, and enzyme activity of CYPs in rats. Experimental Design: Two groups of animals (A-75 and A-150) were treated with four doses of CPA (75 and 150 mg/kg, respectively) at short time intervals (6 h). The third group of animals (B-150) was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…A significant finding of this study was that maximal changes in gene expression, in most cases, were observed at the first time point evaluated (0.5 days), with the exception of CYP3a11 at Day 2 and CYP1a1 at Day 4. This transcriptional induction at an early time point has been observed in other studies (Goodsaid et al, 2003;Afsharian et al, 2007). The early maximal induction subsided to an elevated level, compared with the control.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A significant finding of this study was that maximal changes in gene expression, in most cases, were observed at the first time point evaluated (0.5 days), with the exception of CYP3a11 at Day 2 and CYP1a1 at Day 4. This transcriptional induction at an early time point has been observed in other studies (Goodsaid et al, 2003;Afsharian et al, 2007). The early maximal induction subsided to an elevated level, compared with the control.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, we and others demonstrated the utility of transcriptional CYP analysis in rat studies (Goodsaid et al, 2003;Xie et al, 2005;Afsharian et al, 2007). Several studies reported good correlations in mouse with single or multiple time points (Martignoni et al, 2006;PustyInyak et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…WRL68 normal liver cell line was used to proceed with combination treatment of C. vespertilionis ethanolic extract and cyclophosphamide. This is because cyclophosphamide is extensively metabolized in the liver by cytochrome P450 enzymes via activation process 4hydroxylation producing active metabolite, 4hydroxycyclophosphamide that penetrates the cell membrane which then decomposes to phosphoramide mustard that alkylates DNA 25 . The combination index derived from the combination treatment tabulated in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription of CYP2J2 , known to metabolize cyclophosphamide [ 64 ], was upregulated in the tumors by chemotherapy alone and by combination therapy. This upregulation of CYP2J2 is not surprising as exposure to cyclophosphamide can increase the transcription and expression of cyclophosphamide metabolizing enzymes [ 69 ]. Ultimately, more research is needed to truly understand the complex mechanisms involved in herb–drug interactions and their impact on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%